Observation of the domain wall propagation in CoFe and CoFeB nanowires driven by sub-nanosecond magnetic pulse using micromagnetic simulation. Issue 1 (February 2020) - Hawibowo, S; Kurniawan, C; Djuhana, D
Abstract: In this study, we have observed the domain wall (DW) propagation in CoFe and CoFeB nanowires driven by sub-nanosecond magnetic pulse using micromagnetic simulation approach. The length of the nanowire is 2000 nm, the widths are varied of 50, 100, and 150 nm, and the thicknesses are 2.5 and 5.0 nm. The simulation was performed using a rectangular cell size of 5×5× t nm 3 with t is the thickness of the nanowire and the damping factor is 0.05. The sub-nanosecond magnetic pulse length of 0.5 ns was used to move DW through the nanowire. We found that the DW velocity increased as the magnitude of magnetic pulse increased then abruptly decreased which known as the Walker Breakdown ( H WB ). The transverse type DW structure is observed below the H WB field while vortex/anti-vortex wall structure was formed above H WB . We found that the H WB value of CoFe and CoFeB decreased as the width and thickness of the nanowire increased. The increasing of nanowire thickness also caused the velocity reduction of DW. The energy competition between exchange and demagnetization energy contributed to the DW structure during propagation. The exchange energy is higher than the demagnetization energy as the formation of vortex/anti-vortex wall.